The Analisis Penerapan Metode RCM dan FMECA Untuk Meningkatkan Efesiensi Mesin Produksi di PT. XYZ - Mulyadi, Mulyadi; Hermawan, Asep; Oetomo, Dedi Setyo (Universitas Muhammadiyah Sorong, 2026)
Nowadays, achieving customer satisfaction and gaining their trust is becoming increasingly difficult. This can be achieved by increasing product quality, one way to fulfill it is by performing optimal machine maintenance. This study aims to understand the maintenance of the Winder Barmag Wings 12 end production machine and provide maintenance suggestions using the Reliability Centered Maintenance (RCM) method and the failure mode effect criticality analysis (FMECA) method. RCM to create an effective maintenance strategy to increase machine life and reduce maintenance costs and FMECA to identify potential failures in a system, analyze their impact, and determine the criticality level of the failure. The results of the FMECA analysis show that the birotor abnormality is the dominant cause of damage with a Risk Priority Number (RPN) value of 512 and a criticality of 7.466. The repair recommendation is to immediately replace the birotor part from OEM China to the OEM Barmag birotor part and the result is an RPN value of 18 and a criticality of 0.225 and after calculating the cost difference before and after repairing the birotor replacement of PT. XYZ achieved cost savings of 51,619,200.00.